A Corpus-Based Halliday’s Transitivity Analysis of ‘To the Lighthouse’ - Um-e- Ammara; Rehana Yasmin Anjum; Maryiam Javed (Linguistics and Literature Review, 2019)
This study explores transitivity in the novel “To the Lighthouse” (1927) by Virginia Woolfs as one of the methods of clause analysis in the ideational meta-function of language. The transitivity analysis was carried out by using AntConc 3.5.7 corpus analysis tool software, through which the text of the novel was first tagged and then analysed. This was clause analysis and all the types of processes, participants and circumstances were investigated. The research is for language researchers to analyse and interpret text of different genres of literature.